A SAFETY DRIVEN REVIEW OF WEARABLE AND A PROPOSED SAFETY FRAMEWORK - Olanrewaju, O. M.; Adebiyi, Faith O. (FUDMA JOURNAL OF SCIENCES, 2023)
As computers move from the desktop, to the palm top, and onto our bodies and into our everyday lives, infinite opportunities arise to realize various applications that have never before been possible. As wearable technologies such as the Google Glass, Earbuds are developed and released to the public, health problems resulting from volume of rays that are penetrating human bodies through the signal emissions from these devices must be acknowledged and accounted for. This paper presents wearable computer devices their uses, hazards and the need for the adoption of global safety standards in order to make them safe for users. It also proposed a framework for evaluating the safety use of the wearable devices.
Keywords: wearable, emissions, hazards, standards, EMI, SAR